Europeanization of Türkiye’s Climate Change Policies - Özan, Özlem (Fırat University, 2025)
In recent years, climate change has become the most important problem affecting life on earth. Faced with this problem, governments have started to take various measures at local, regional and international levels. In particular, the European Union (EU) has emerged as a strong actor in climate change policies and contributed to the development of climate change legislation at both national and international level. The EU has also influenced the climate change policies of Türkiye, which is both a candidate country for EU membership and one of the countries most affected by climate change. Therefore, the aim of this study is to examine how and to what extent Türkiye’s climate change policies have been affected by EU policies and to evaluate the results of these effects within the framework of Europeanization. Europeanization is defined as the influence of the EU on the domestic policies and institutional structures of member and candidate countries and allows for the evaluation of the consequences of this influence. This study is planned to consist of three parts. In the first part, the theoretical framework of the study will be explained, focusing on the concept of Europeanization and the changes and consequences it has led to in member and candidate countries. In the second part, climate change and its impacts on Türkiye will be evaluated and Türkiye’s climate change policies will be discussed. In the third part, how and to what extent the EU has affected Türkiye in the field of climate change will be examined within the framework of Europeanization.

Son yıllarda iklim değişikliği, dünya üzerindeki yaşamı etkileyen en önemli sorun haline gelmiştir. Bu sorunla karşı karşıya kalan hükümetler yerel, bölgesel ve uluslararası düzeyde çeşitli önlemler almaya başlamıştır. Özellikle Avrupa Birliği (AB), iklim değişikliği politikalarında güçlü bir aktör olarak ortaya çıkmış, hem ulusal hem de uluslararası düzeyde iklim değişikliği mevzuatının geliştirilmesine katkıda bulunmuştur. AB, hem AB üyeliğine aday bir ülke hem de iklim değişikliğinden en çok etkilenen ülkelerden biri olan Türkiye’nin iklim değişikliği politikalarını da etkilemiştir. Dolayısıyla bu çalışmanın amacı, Türkiye'nin iklim değişikliği politikalarının AB politikalarından nasıl ve ne ölçüde etkilendiğini incelemek ve bu etkilerin sonuçlarını Avrupalılaşma çerçevesinde değerlendirmektir. Avrupalılaşma, AB’nin üye ve aday ülkelerin iç politikaları ve kurumsal yapıları üzerindeki etkisi olarak tanımlanmakta ve bu etkinin sonuçlarının değerlendirilmesine olanak sağlamaktadır. Bu çalışmanın üç bölümden oluşması planlanmaktadır. İlk bölümde çalışmanın teorik çerçevesi açıklanacak, Avrupalılaşma kavramına ve bunun üye ve aday ülkelerde yol açtığı değişim ve sonuçlara odaklanılacaktır. İkinci bölümde iklim değişikliği ve Türkiye’deki etkileri değerlendirilecek ve Türkiye’nin iklim değişikliği politikaları tartışılacaktır. Üçüncü bölümde ise AB’nin iklim değişikliği alanında Türkiye’yi nasıl ve ne ölçüde etkilediği Avrupalılaşma çerçevesinde incelenecektir.
Türkiye’nin İklim Değişikliği Politikalarının Avrupalılaşması
Keywords: Climate Change Impacts and Adaptation (Other); İklim Değişikliği Etkileri ve Uyarlama (Diğer)